Envisioning a New European Bauhaus Stage (EAAE Annual Conference Proceedings, 2023)
The stage workshop was integral to the historical Bauhaus. Experimenting with dance and theater, it added body, space, and movement studies to the design curriculum. The interdisciplinary “High-Level Roundtable” of the New European Bauhaus initiative falls somewhat short in representing this field. Therefore, this paper literally calls to action. It outlines the importance of a New European Bauhaus Stage, speculates on how such a project may look like, and critically reflects on its promises and pitfalls. What can we learn from the historical Bauhaus Stage? What can the disciplines of dance and theater offer to contemporary design and architecture education? How can the initiative contribute to a “sustainable and inclusive future”, as envisioned by the overarching project?